Weaving the Fabric of Public Policies: Comparing and Integrating Contemporary Frameworks for the Study of Policy Processes. Issue 3 (26th May 2016) - Howlett, Michael; McConnell, Allan; Perl, Anthony
Abstract: For close to three decades multiple frameworks of policy-making have served as competitive characterizations of policy processes. All claim to provide accounts that capture diverse factors such as changing governance norms, actors and ideas which drive programme interventions and policy outputs. Paradoxically, the resilience of different models such as the policy cycle framework and the multiple streams framework has been accompanied by numerous critiques that they are "incomplete" and even divorced from the real world. This article presents an effort to synthesize and reconcile these frameworks in which the appeal and strengths of each can be retained while going some way to overcoming their weaknesses and limitations. It does so through the introduction of an integrative metaphor for policy-making – what Wayne Parsons termed "weaving" – which can be applied to all stages of public policy, and is flexible enough to cope with issues such as power, complexity and critical junctures while reconciling different groupings and sets of actors highlighted as significant policy players in earlier models. It elaborates this framework before applying it by way of illustration to one of the most controversial policy initiatives in modern British history: the 1989–93 poll tax. The article and case study highlight the potential for its general application in policy studies.